Electro-Thermal Modeling of Large Format Lithium-Ion Pouch Cells: A Cell Temperature Dependent Linear Polarization Expression. Issue 14 (16th November 2016) - Rheinfeld, Alexander; Kosch, Stephan; Erhard, Simon V.; Osswald, Patrick J.; Rieger, Bernhard; Jossen, Andreas
Abstract : In the work presented here, a well-known semi-empirical electro-thermal model of large format lithium-ion pouch cells is extended by accounting for a cell temperature dependency of electrode polarization gained from full cell measurement. For model parametrization, the cell was discharged at varying discharge rates and ambient temperatures within a climate chamber. By relating the measured cell potential to its current temperature, a cell temperature dependency of cell polarization is established. Evaluating the advantages of this approach, the extended model is compared to the initial model regarding the quality of predicting the electrical and thermal cell behavior. For further means of model validation, the cell was investigated at cooling conditions varying from the parametrization measurements via infrared thermography. It can be shown that a temperature dependency of electrode polarization shows superior quality especially when predicting the overall electrical and thermal cell performance at ambient conditions varying from the parametrization scenario. Controlling the thermal boundary conditions further allows to evaluate the impact of local heat generation on the temperature distribution. For a laminar, directed airflow of 1 m/s along the cell, the influence of local heat generation is minor in comparison to the thermal boundary conditions prevailing at the cell's surface and tabs.